Greuze, 1725-1805 / by Beatrice A. Waldram. - Waldram, Beatrice A. (Tufts University. Tisch Library., 2019)
1 online resource (96 pages, 8 unnumbered leaves of plates) : color illustrations; Includes index.; Electronic reproduction. Medford, MA : Tisch Library, Tufts University, 2018. Scanned by the Boston Library Consortium/Open Content Alliance as part of the BLC OCA Digitization Project from a copy at the Tisch Library, Tufts University.